VD_FINDINFO HC / 2025 / 212 vom 7. Juli 2025 - VD Tribunal cantonal (2025)
RÉSILIATION ABUSIVE, PERTE DE GAIN, DROIT AU SALAIRE | 18 CO, 322 al. 1 CO, 322a CO, 322d CO, 323 al. 1 CO, 323b CO, 324a al. 1 CO, 324a al. 2 CO, 324a CO, 327a al. 2 CO, 328 CO, 335 al. 1 CO, 335 al. 2 CO, 335a CO, 335c al. 1 CO, 336 al. 1 let. d CO, 336a al. 1 CO, 336a al. 2 CO, 336a CO, 337 al. 1 CO, 339 CO, 43 al. 1 CO, 44 CO, 49 CO, 97 CO, 227 al. 1 CPC (CH)